Banking on Terminology Conference Interpreters in the Electronic Age - Moser-Mercer, Barbara (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1992)
AbstractConsiderable effort has already been spent on devising terminology documentation guidelines and it has always been assumed that interpreters' needs are identical to those of translators and terminologists. While members of the three professions are all agreed on the need for the proper term and/or phrase to denote an object or an idea, considerable differences exist in the way these professionals gain access to terminological information. This paper sketches the differences in the flow of work of translators and interpreters. Information on interpreters' terminological needs was gathered by means of a questionnaire sent out to members of the International Association of Conference Interpreters (AIIC) and the statistical analyses are presented with specific reference to terminological data elements, documentation control and data exchange among conference interpreters.